THE EFFECT OF PROVIDING BAGLOG WASTE FEED OF WHITE OYSTER-MUSHROOMS (Pleurotus ostreatus) AND CHICKENâS FECES UPON THE COCOONâS GROWTH AND PRODUCTION OF THE EARTHWORMS (Lumbricus rubellus) AS THE RESOURCE OF BIOLOGY INSTRUCTION - Pangestika, Dika Satya (Jurnal Pendidikan Biologi Indonesia, 2016)
Earthworms (Lumbricus rubellus) are commonly utilized as a feed that contains lot of proteins needed by poultry, such as aves, fish, and shrimps. The effort of improving earthworms (Lumbricus rubellus) harvesting, in fact, is affected by the soar of the feedâs price as well. Earthworm (Lumbricus rubellus) breeders must be more innovative in finding the alternative food for the earthworms.This research employed Completely Randomized Design design through four treatments and two repetitions. In addition, the sample constituted the 640 ciliated earthworms (Lumbricus rubellus) by using randomized sampling technique. This research revealed that providing baglog waste feed of white oyster-mushrooms, the chickensâ feces, and the combination of the two gave a significantly highest effect (based on sig.<0,05) upon the cocoonâs growth and production of the earthworms (Lumbricus rubellus) in treatment A3B3 (10 cm), the heaviest mass of the earthworms was in treatment A3B3 (4.00 grams), and the highest production of cocoon was in treatment A3B3 (64.5 items). There was an effect of providing baglog waste feed of white oyster-mushrooms, the chickensâ feces, and the combination of the two upon the growth and the production of the earthwormsâ cocoon. Further, the result of this research could be used as the resource of Biology instruction due to the appropriateness and the qualification that met the six vital aspects; they were: (1) potential clearance; (2) appropriateness to instructional goals; (3) target consideration; (4) informational clearance; (5) exploration clearance; and (6) acquisition clearence.Â